The eyespot and behavioral light responses - Kreimer, Georg; Wakabayashi, Ken Ichi; Hegemann, Peter; Dieckmann, Carol (Elsevier, 2023)
Chlamydomonas cells respond to light by adjusting swimming behavior to reach optimal exposure levels for photosynthesis. This phototactic behavior depends on a light driven signal transduction pathway that is organized spatially and temporally. Channelrhodopsins (CHRs), retinal based photoreceptors, reside in the eyespot, a complex organelle comprising four different membranes and carotenoid rich globules. The precisely spaced eyespot layers function as an optical device that promotes directional light detection. Asymmetric placement of the eyespot relative to the microtubule cytoskeleton and paired cilia is required for phototaxis via changes in the ciliary breaststroke waveform that powers movement. This chapter reviews what is known about eyespot composition and placement, signal transduction from light reception by the CHRs to ciliary responses, modulation of phototactic behavior by intracellular and environmental factors, and methods for analyzing photomovement of both single cells and populations. Proteins and enzymes important for eyespot biogenesis and phototaxis, discovered through a combination of biochemical and genetic approaches, are highlighted.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Channelrhodopsin; cilia; eyespot assembly and placement; eyespot proteins; light induced ciliary responses; photophobic/photoshock response; photoreceptor current and signaling; phototactic sensitivity; phototaxis